Dispersive liquid–liquid microextraction and preconcentration of thallium species in water samples by two ionic liquids applied as ion-pairing reagent and extractant phase - Escudero, Leticia Belén (2012)
In the present work, a simple and highly sensitive analytical methodology for determination of Tl+ and Tl3+ species, based on the use of modern and non-volatile solvents, such as ionic liquids (ILs), was developed. Initially, Tl+ was complexed by iodide ion at pH 1 in diluted sulfuric acid solution. Then, tetradecyl(trihexyl)phosphonium chloride ionic liquid (CYPHOS® IL 101) was used as ion-pairing reagent and a dispersive liquid?liquid microextraction (DLLME) procedure was developed by dispersing 60 mg of 1-hexyl-3-methylimidazolium hexafluorophosphate [C6mim][PF6] with 500 L of ethanol in the aqueous solution. After the microextraction procedure was finished, the final IL phase was solubilized in methanol and directly injected into the graphite furnace of an electrothermal atomic absorption spectrometer (ETAAS). An extraction efficiency of 77% and a sensitivity enhancement factor of 100 were obtained with only 5.00 mL of sample. The limit of detection (LOD) was 3.3 ng L-1 Tl while the relative standard deviation (RSD) was 5.3% (at 0.4 µg L-1 Tl and n = 10), calculated from the peak height of absorbance signals. The method was finally applied to determine Tl species in tap and river water samples after separation of Tl3+ species. To the best of our knowledge, this work reports the first application of ILs for Tl extraction and separation in the analytical field.